2009
DOI: 10.1590/s0103-90162009000500009
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals extractability in a soil amended with sewage sludge

Abstract: Few investigations have been carried out about the comparison of desorption rate and amount of heavy metals extracted successively by organic acid mixtures mimicking the rhizosphere and routine extractants in sewage sludge-amended soils. Extractions of Zn, Cd, Ni, Cr, and Cu were performed in samples of a sewage sludge-amended soil using seven extractants: four organic acid mixtures and three routine extractants (DTPA, Mehlich-I, and ammonium acetate). Results from single pass extractions, in which the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…He and Singh (1993) assigned increased extractability of Cd by DTPA to decrease in pH caused by decomposition of sludge-borne organic matter. Among seven extractants (DTPA, Mehlich-I, NH 4 OAc, and four organic acid mixtures) studied by Marchi et al (2009), DTPA presented a high extractability of Cd and Ni as well as the highest rates of extraction in a soil amended with sewage sludge. Despite higher total Cr levels than the total Pb levels in the experimental sludge, the extractability of Cr by DTPA was much lower than that of Pb at all rates of sludge application.…”
Section: Dtpa-extractable Heavy Metalsmentioning
confidence: 98%
“…He and Singh (1993) assigned increased extractability of Cd by DTPA to decrease in pH caused by decomposition of sludge-borne organic matter. Among seven extractants (DTPA, Mehlich-I, NH 4 OAc, and four organic acid mixtures) studied by Marchi et al (2009), DTPA presented a high extractability of Cd and Ni as well as the highest rates of extraction in a soil amended with sewage sludge. Despite higher total Cr levels than the total Pb levels in the experimental sludge, the extractability of Cr by DTPA was much lower than that of Pb at all rates of sludge application.…”
Section: Dtpa-extractable Heavy Metalsmentioning
confidence: 98%
“…While there are numerous studies that deal with sorption capacity of biochars for heavy metals when applied to soil in light of phytoremediation perspective (Cao et al, 2009;Namgay et al, 2010;Uchimiya et al, 2011), studies regarding on leachability (through desorption or dissolution) of heavy metals from biochar and their bioavailability are virtually nonexistent. The heavy metals, however, are known to be desorbed by naturally occurring organic acids such as citric, oxalic, acetic, and lactic acids (Nascimento, 2006;Marchi, 2009) and dissolved organic carbon (Antoniadis & Alloway, 2002) from soils amended with sewage sludge. Regardless of equilibrium amounts of Cd adsorbed in an Andisol, more than 80% of Cd was desorbed with one time extraction with citric acid if its concentration was more than 0.1 M, and more than 90% was recovered if five soil pore volumes of 0.1 M citric acid were continuously run through the Cd-contaminated soil (Abe et al, 2004).…”
Section: Heavy Metal Leachability From Biocharmentioning
confidence: 99%
“…Marchi et al [81] compared the amount of elements extracted from biosolids-amended soils by four organic acid mixtures that mimic the compositions of organic acids in the rhizosphere and three reagents commonly used for trace element extraction, namely DTPA-TEA [73], Mehlich-I [77], and ammonium acetate [82]. They showed that the one-time extraction did not remove all of the extractable elements in the soils.…”
Section: Source Assessmentmentioning
confidence: 99%